Upregulation of microRNA miR-652-3p is a prognostic risk factor for hepatocellular carcinoma and regulates cell proliferation, migration, and invasion. Issue 1 (1st January 2021) - Chi, Xiaobin; Jiang, Yi; Chen, Yongbiao; Lv, Lizhi; Chen, Jianwei; Yang, Fang; Zhang, Xiaojin; Pan, Fan; Cai, Qiucheng
ABSTRACT: As powerful regulatory factors, microRNAs (miRNAs) are involved in tumor progression. The current research aimed to excavate the prognostic significance and potential regulatory mechanisms of miR-652-3p in hepatocellular carcinoma (HCC). Expression of miR-652-3p in HCC tissues and cells was exposed by Quantitative real-time polymerase chain reaction (RT-qPCR) assay, and we found that miR-652-3p was elevated in HCC tissues and cells than in the control group ( P < 0.05). Then, the relationship between miR-652-3p levels and clinical characteristics was obtained from the Chi-square test. Kaplan-Meier survival analysis and Cox regression model to explore the outcome of miR-652-3p on the prognosis of HCC. The results investigated that overexpression of miR-652-3p was related to clinical tumor-node-metastasis (TNM) stage ( P = 0.020) and differentiation ( P = 0.031). HCC patients with elevated miR-652-3p levels were correlated with poor overall survival (log-rank, P = 0.007), and maybe a possible prognostic marker for HCC. Finally, CCK-8, colony formation, wound healing and Transwell assay was detected after transfection of HCC cells with miR-652-3p mimic or inhibitor. And the results confirmed that elevation miR-652-3p promoted the proliferation, migration, and invasion of tumor cells ( P < 0.05). All data indicated that elevated miR-652-3p is a prognostic marker and would be able to participate in tumor progression of HCC by regulating cell proliferation, migration, and invasion.